1973
DOI: 10.1002/prac.19733150306
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerie und Nomenklatur der „Pyrazolone”︁ und Amino‐pyrazole

Abstract: Für die „Pyrazolone”︁ wird eine einheitliche und logische Nomenklatur empfohlen, wobei alle N‐substituierten „Pyrazolone”︁ als Derivate der vier praktisch bedeutsamen Tautomeren des Grundkörpers, d.h. des 3‐Hydroxy‐pyrazols 1, Delta;4‐Pyrazolinons‐(3) 2, Δ2‐Pyrazolinons‐(5) 3 und 5‐Hydroxy‐pyrazols 4 aufgefaßt werden. Die „Pyrazolone”︁ sollten in Zukunft nach der tautomeren Form benannt werden, die allgemein bzw. in verdünnter, indifferenter Lösung bevorzugt vorliegt. Basierend auf kritisch eingeschätzten Lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

1974
1974
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(7 citation statements)
references
References 46 publications
0
4
0
3
Order By: Relevance
“…For unsubstituted 3(5)-aminopyrazoles, one of the first experimental studies of tautomerism, accomplished by Dorn, was based on IR and 1 H-NMR techniques [110]. In this study, the author found a higher abundance of the 3-amino tautomer in solution, contradicting some results obtained to that date.…”
Section: Experimental Studiesmentioning
confidence: 73%
See 1 more Smart Citation
“…For unsubstituted 3(5)-aminopyrazoles, one of the first experimental studies of tautomerism, accomplished by Dorn, was based on IR and 1 H-NMR techniques [110]. In this study, the author found a higher abundance of the 3-amino tautomer in solution, contradicting some results obtained to that date.…”
Section: Experimental Studiesmentioning
confidence: 73%
“…Tautomerism in 3(5)-aminopyrazoles has to be carefully appraised by chemists, on account of the specificities inherent to this scaffold that impact in reactivity and synthesis. Several experimental [50,72,93,[109][110][111] and theoretical studies [43,60,64,70,72,84] were carried out, the majority focusing on the structural aspects and corroborating the general conclusions applicable to the pyrazole family.…”
Section: Tautomerism In 3(5)-aminopyrazolementioning
confidence: 73%
“…2 Mol Isocya-naten gibt es in der Literatur unterschiedliche Angaben. Wahrend einige Autoren eine 1 -Acyl-5-acylamino-Struktur (E4) angeben [24,29], formulieren andere Autoren eine 1 -Acyl-3-acylamino-Struktur (E5) [22, 251. Die 'H-und 13C-NMR-spektroskopischen Werte zeigen, dafl alle oben beschriebenen zweifach acylierten Amino-pyrazole als 1-Acyl-3-acylaminopyrazole E5 vorliegen.…”
Section: N-diacylierte Amino-pyrazoleunclassified
“…This is particularly critical in the case of the non-substituted 3(5)-aminopyrazoles, for which, to the best of our knowledge, no previous experimental studies have been reported hitherto in the gas phase (or for the isolated molecules in general), while the theoretically available data are also very limited. Previously reported experimental investigations on 3(5)-aminopyrazoles have been carried out for a few substituted compounds in solution or in the solid state, either by NMR spectroscopy or X-ray diffraction [9][10][11][12], while past theoretical studies on 3(5)-aminopyrazoles focused mostly on the evaluation of the relative stabilities of the 3-amino vs. the 5-amino tautomer in the gas phase or in solution [13][14][15][16]. The last studies indicated that the 3-amino tautomer is more stable than the 5-amino tautomer, but the relative stability of pyrazole tautomers have been found to be very much dependent on the nature of the substituents [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%